Afterword: Reflections on Early Modern Women in the Low Countries and Beyond - Wiesner-Hanks, Merry (Early Modern Low Countries, 2025)
This afterword reflects on the articles in this special issue, and places them within the context of other historiographic surveys of early modern women, including three from the 1990s and two more recent ones. It highlights similarities and differences in the scholarship on the Low Countries and that of other parts of Europe, and points particularly to common trends, including an emphasis on women’s actions and agency rather than representations of women or men’s ideas about women; a stress on specific spaces and routes, including the Atlantic World; the importance of material culture in examining many kinds of topics; a broadening of the notion of ‘literature’ and ‘art’ to include a wider range of genres and makers; attention to differences among women and the ways these intersected with gender; the growing use of digital technologies; and the importance of trans-disciplinary and sometimes transnational collaborations. Methods and theories developed in the Low Countries have provided models for other parts of Europe, and those developed elsewhere have sometimes been applied in the Netherlands, though more of this is possible.